Seizing the Means of Reproduction : Entanglements of Feminism, Health, and Technoscience - Murphy, Michelle (Claudette Michelle) (Book collections on Project MUSE., 2012)
In Seizing the Means of Reproduction, Michelle Murphy's initial focus on the alternative health practices developed by radical feminists in the United States during the 1970s and 1980s opens into a sophisticated analysis of the transnational entanglements of American empire, population control, neoliberalism, and late-twentieth-century feminisms. Murphy concentrates on the technoscientific means -- the technologies, practices, protocols, and processes -- developed by feminist health activists. She argues that by politicizing the technical details of reproductive health, alternative feminist practices aimed at empowering women were also integral to late-twentieth-century biopolitics.